2019
DOI: 10.32718/nvlvet9508
|View full text |Cite
|
Sign up to set email alerts
|

The influence of silicium compounds on the content of calcium, phosphorus and some lipides in the plasma blood

Abstract: The aim of the study was to investigate the effects of nanotechnology and sodium metasilicate on the content of total calcium and inorganic phosphorus and individual lipids in the blood of rabbits from 52 to 110 days of life. Studies were conducted on young rabbits of Hyla breed in the private sector. Rabbits for the study were selected at the age of 41 days on the principle of analogues, weighing 1.2–1.4 kg, were divided into six groups (control and five experimental), 6 animals (3 males and 3 females) in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The absorption of phosphorus in young animals is very likely to be more active than in adults. Our studies revealed the influence of compound of zinc citrate on the activation of processes of digestion of phosphorus in the organism of rabbits after weaning, as confirmed by young animals subjected to the influence of nanoaquachelate of the microelement (Ivanitskaya et al, 2019). An important indicator of balanced diet of animals, especially fast-growing young rabbits, is the ratio of calcium and phosphorus in their organism.…”
Section: Discussionsupporting
confidence: 59%
“…The absorption of phosphorus in young animals is very likely to be more active than in adults. Our studies revealed the influence of compound of zinc citrate on the activation of processes of digestion of phosphorus in the organism of rabbits after weaning, as confirmed by young animals subjected to the influence of nanoaquachelate of the microelement (Ivanitskaya et al, 2019). An important indicator of balanced diet of animals, especially fast-growing young rabbits, is the ratio of calcium and phosphorus in their organism.…”
Section: Discussionsupporting
confidence: 59%